AHLI WARIS SAUDARA DAN ANAK KANDUNG MENURUT HUKUM WARIS ISLAM - Nanda Septianingtyas; Khairani Bakri (Fakultas Hukum Universitas Trisakti, 2022)
The Qur'an, Hadith, and Ijtihad serve as the foundation for Islamic inheritance law. Ijbari-based inheritance in Islam places children, parents, widows or widowers, and siblings among the heirs. creation of the issue 1) How does Islamic inheritance law treat siblings inheriting alongside their biological children? 2) How acceptable is the Majalengka Religious Court's ruling on the identification of the deceased person's heirs, Majalengka Religious Court Number 0457/Pdt.P/2020/PA.Mjl? Islamic Inheritance Law in Cuminah? Normative research is the kind of study that researchers employ. Descriptive research is the type that was used. With primary and secondary legal resources, secondary data is utilised. Data is qualitatively evaluated, and deductive reasoning is used to reach conclusions. Conclusion: You will not be able to obtain an inheritance if the heir still has biological children and the Judge's Determination is not in accordance with the Al-Qur'an Surah An-Nisa verse (176) in conjunction with Articles 174 and 182 KHI.